2019
DOI: 10.3389/fendo.2019.00059
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones and Cancer: A Comprehensive Review of Preclinical and Clinical Studies

Abstract: Thyroid hormones take major part in normal growth, development and metabolism. Over a century of research has supported a relationship between thyroid hormones and the pathophysiology of various cancer types. In vitro studies as well as research in animal models demonstrated an effect of the thyroid hormones T3 and T4 on cancer proliferation, apoptosis, invasiveness and angiogenesis. Thyroid hormones mediate their effects on the cancer cell through several non-genomic pathways including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
117
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(124 citation statements)
references
References 220 publications
(245 reference statements)
1
117
2
4
Order By: Relevance
“…Moreover, it has been reported that GC accumulates triiodothyronine (T3) through the overexpression of transthyretin involved in cellular T3 import [22]. The increased intracellular T3 concentration directly contributes to cancer progression, by different pathways [23]. In human surveys, similarly, iodine prophylaxis was effective in decreasing the incidence and death rate for GC in iodine-deficient areas [24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that GC accumulates triiodothyronine (T3) through the overexpression of transthyretin involved in cellular T3 import [22]. The increased intracellular T3 concentration directly contributes to cancer progression, by different pathways [23]. In human surveys, similarly, iodine prophylaxis was effective in decreasing the incidence and death rate for GC in iodine-deficient areas [24].…”
Section: Introductionmentioning
confidence: 99%
“…For years, it has been established that both Graves' disease [15] and hyperthyroidism in general [16] are causative of an increasing cancer incidence. As larger thyroids and more severe hyperthyroidism in Graves' disease are in clinical practice associated with higher activities necessary for effective treatment, it could very well be that it is the hyperthyroidism per se that is causing the excess cancer mortality-there is a considerable body of evidence showing this.…”
mentioning
confidence: 99%
“…The promoter region of GPD2 contains thyroid hormone response elements (TRE) which respond to the thyroid hormones, particularly triiodothyronine (T3), that can activate mGPDH transcription in a tissue-specific manner. This information is particularly important since T3 has been shown as cancer growth promoting factor in many cancer models, including breast, prostate, thyroid, lungs and renal cancer [3]. In fact, in a recent study, we observed T3mediated upregulation in mGPDH expression in human thyroid cancer cells [4].…”
Section: Breathing the Air Of Mitochondrial Respiration Via An Importmentioning
confidence: 71%